Manajemen Usahatani Jagung Lokal di Kabupaten Bangkalan - Fajariyah, Miraty Segundary; Wijayanti, Dian Eswin (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
Farming business are important to implement management functions in order to get good results and be more efficient in managing so as to earn good income. The purpose of this study was to determine the management of local corn farming in Geger Sub-district, Bangkalan District. The sampling method of location done by purposive sampling. Determination of the sample with snowball sampling technique with a sample 20 farmer local corn. This study use a qualitative with descriptive method. Method of data collection using primary data and secondary data. The primary data were obtained from in-depth observations and interviews with field extension officer and farmer group leader. Meanwhile, secondary data was obtained from all relevant parties including the Department of Agriculture in Bangkalan, the Central Bureau Statistics (BPS), the Agricultural Extension Agency (BPP), as well as journals relevant to the research topic. The results showed that local corn farming in Bangkalan Regency was profitable because the R/C ratio was >1. Management of corn farming in Bangkalan Regency has carried out activities that include farming management functions ranging from planning, organizing, actuating, and controlling.